The inverse of the function f(x) = 3x + 5 is
![f^(-1)(x) = (x - 5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/n4yebamgmhuj2oocqaa3schiic0wnrq39s.png)
How to determine the inverse of the function
From the question, we have the following parameters that can be used in our computation:
f(x) = 3x + 5
Express the function as an equation
So, we have
y = 3x + 5
Swap the occurrence of x and y in the equation
This gives
x = 3y + 5
Subtract 5 from all sides
3y = x - 5
So, we have
![y = (x - 5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/scy05bl6i4wqk3ozn6drxt440v2bo5l8u2.png)
Express as an inverse function
![f^(-1)(x) = (x - 5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/n4yebamgmhuj2oocqaa3schiic0wnrq39s.png)
![f^(-1)(x) = (x - 5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/n4yebamgmhuj2oocqaa3schiic0wnrq39s.png)
Verifying the relationship
and
![f(f^(-1)(x))](https://img.qammunity.org/2020/formulas/mathematics/college/ybuem3iurdjn70ma9swhowymlyr35tydvs.png)
We have
![f^(-1)(f(x)) = (3x + 5 - 5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/vd28l2823jiwwi0icx50oz7dzlphopin9i.png)
![f^(-1)(f(x)) = (3x )/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/vh11vmw3clu2kdrg4ckyodpddd2wg6yhia.png)
![f^(-1)(f(x)) = x](https://img.qammunity.org/2020/formulas/mathematics/college/b041k7gtomjug86oue1thmxvorii6fbq1d.png)
Also, we have
![f(f^(-1)(x)) = 3 * (x - 5)/(3) + 5](https://img.qammunity.org/2020/formulas/mathematics/college/up6t5a1lsguqxio8s9hckmlnm22tlpc7wl.png)
![f(f^(-1)(x)) = x - 5 + 5](https://img.qammunity.org/2020/formulas/mathematics/college/dp43sz8qizwtzgcjel3h7ozzzjktgim9gi.png)
![f(f^(-1)(x)) = x](https://img.qammunity.org/2020/formulas/mathematics/college/jd0ds8z0kdifo0j6jn3j1obtgj0h6k0t4s.png)
Hence, the inverse of the function is
![f^(-1)(x) = (x - 5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/n4yebamgmhuj2oocqaa3schiic0wnrq39s.png)
Question
Find the inverse of the function below and write it in the form y = f^-1(x)
Verify the relationshipsf(f^-1(x)) and f^-1(f(x))=x
f(x)=3x+5